ФОРМУВАННЯ ПОЗИТИВНОГО СТАВЛЕННЯ ДО УРОКІВ ФІЗИЧНОЇ КУЛЬТУРИ У ШКОЛЯРІВ ЧЕРЕЗ ВИХОВАННЯ СУЧАСНОГО ПЕДАГОГА - Андріанов T.V.; Марчик V.I.; Андріанов V.E. (Educational Dimension, 2004)
It Is Determined that actions, which effectively raise the interest a pupil to physical culture, are found in border professional strong, bright, enthusiastic personality - a teacher of the physical culture, which actively propagandizes the ideas of the physical culture and sport.